If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-1=9(x+3)
We move all terms to the left:
2x-1-(9(x+3))=0
We calculate terms in parentheses: -(9(x+3)), so:We get rid of parentheses
9(x+3)
We multiply parentheses
9x+27
Back to the equation:
-(9x+27)
2x-9x-27-1=0
We add all the numbers together, and all the variables
-7x-28=0
We move all terms containing x to the left, all other terms to the right
-7x=28
x=28/-7
x=-4
| 2,5=3x | | 3(x+5)-2x=11+x+4 | | 4x5+10=6 | | 42=6d-6 | | x+6=-183 | | 3÷7x+6=9 | | 5x+15=30x-45 | | 23-4n=n*n-22 | | C=30x+1,000 | | f(-2)=-3+4 | | 6+18=h(3+9) | | 1p-8=10+7p | | 2x−11=48 | | 7=6–4y+4y | | 4k-k=6-k | | 3(2x-9=21 | | 3(x+2)-1=3(x+3) | | 16-6x-30=20 | | p/9=17 | | 2x+10=20x-30 | | 50=x-30 | | 26=6-3x | | 6=b/2+2 | | m-25=105 | | (x-4)/2=-6 | | (x-4)/2=-61 | | 13x+12=56x−52 | | x+(-17)=4 | | 5x+20=10x+-5 | | 5(x+2)=-5-2(x-3) | | 7x-1-2x=9+5(x-2 | | x2−3x+4=(x+2)(x−4) |